A Fiqhi and Legal Analysis of Unauthorized Encroachment on the Riverbed and Riparian Zone - Alireza Ebrahimi; Reza Askari (پژوهش‌های فقهی مسائل مستحدثه)
The issue of land occupation and water utilization is a vital matter that requires the establishment of specific regulations. Furthermore, according to Article 45 of the Iranian Constitution and Articles 1 and 2 of the Law on the Fair Distribution of Water, waters are considered public common property, the possession and utilization of which have been entrusted to the Islamic State. To preserve, protect, and ensure the proper utilization of water resources, the preservation of the riparian zone is essential. Following this approach, the Iranian legislature in the Law on the Fair Distribution of Water has designated them as public common property and made the utilization of these waters contingent upon obtaining a permit from the Ministry of Energy. On the other hand, the utilization of waters on private property may conflict with the State’s authority in the utilization of waters. Through the analysis of the descriptions provided in this regard, it was concluded that the lands constructed within the riparian zone of rivers are under the jurisdiction of the State, and their possession is solely considered a right of the State, based on the purport of the Law on the Fair Distribution of Water and its compatibility with the relevant articles of the Civil Code. Similarly, any form of utilization, whether through construction or water extraction, within the riparian zone must be authorized by the Ministry of Energy, even if the land belongs to the municipality or other public legal entities. Furthermore, even in the event that the encroachment on the riparian zone has been carried out with the permission of the relevant organization, the authority to determine its continuation or demolition rests with the Ministry of Energy, in which case the compensation for the owner and the builder will be provided according to Articles 43 and 44 of the same law.